Students’ motivation and ownership in a cross-campus and online setting - Lysne, Dag Atle; De Caro-Barek, Veruska; Støckert, Robin; Røren, Kari Anne Flem; Solbjørg, Ole Kristen; Nykvist, Shaun Sydney (Frontiers in Education, 2023)
This study focuses on student motivation and ownership of learning in a team-based learning environment that is situated in a cross-campus and online context. Data were collected through semi-structured interviews from 12 students who participated in a joint international Master’s degree in Music, Communication and Technology programme between two large Nordic universities. The aim of the study was to identify factors that were most likely to impact student motivation and ownership in this cross-campus and online setting. Three main themes emerged from the analysis of data relating to student motivation and ownership. These three themes were autonomy, peer learning, and communication and social bonding. The study has the potential to contribute to the continued development of future learning environments, which will be physical as well as virtual, or a mix of those. The findings indicated that there is a need to focus on student tasks that should be flexible and open for student choice, and where peer learning is one of the main learning strategies used to engage students. Additionally, the findings also highlight the importance of having a focus on communication and social bonding in the planning and organisation of cross-campus and online courses in order for universities to succeed and to transform to meet the needs of a very diverse group of current and future students.